Implementation of Waste Management Policy in Tanjung Batu Urban Village, Manado City - Cyndi Pratiwi Mananohas; Abdul Rahman Dilapanga; Laurens Bulo (Technium Social Sciences Journal, 2025)
The purpose of this research is to find out, analyze, describe the implementation and determinant factors of the Waste Collection Policy in Tanjung Batu Village, Manado City. This research uses qualitative methods with data collection techniques used are triangulation techniques: observation, interviews and documentation studies. The results showed that the implementation of waste management policies in Tanjung Batu Village, Manado City, was not optimal. Waste sorting at the source level has not gone well due to low community participation, lack of socialization, and lack of adequate sorting facilities. Population awareness of the importance of waste management is still low, so the habit of disposing of waste without sorting remains a common practice. In terms of transportation, delays and breakdowns of waste collection vehicles are common, exacerbated by the lack of human resources and inconsistent behavior of the community in disposing of waste on schedule. The level of community participation in the cleanliness program is also low, influenced by a lack of understanding of the impact of waste on the environment and health, as well as the assumption that waste management is the responsibility of the government or cleaners alone. In addition, compliance with waste management policies is still low, with people often littering. The absence of strict sanctions exacerbates this situation. Determinant factors, such as limited resources, low public awareness, and weak enforcement of sanctions, are the main challenges in improving the effectiveness of waste management in the region.